(4+u)(3u+2)=0

Simple and best practice solution for (4+u)(3u+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4+u)(3u+2)=0 equation:


Simplifying
(4 + u)(3u + 2) = 0

Reorder the terms:
(4 + u)(2 + 3u) = 0

Multiply (4 + u) * (2 + 3u)
(4(2 + 3u) + u(2 + 3u)) = 0
((2 * 4 + 3u * 4) + u(2 + 3u)) = 0
((8 + 12u) + u(2 + 3u)) = 0
(8 + 12u + (2 * u + 3u * u)) = 0
(8 + 12u + (2u + 3u2)) = 0

Combine like terms: 12u + 2u = 14u
(8 + 14u + 3u2) = 0

Solving
8 + 14u + 3u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(4 + u)(2 + 3u) = 0

Subproblem 1

Set the factor '(4 + u)' equal to zero and attempt to solve: Simplifying 4 + u = 0 Solving 4 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + u = 0 + -4 Combine like terms: 4 + -4 = 0 0 + u = 0 + -4 u = 0 + -4 Combine like terms: 0 + -4 = -4 u = -4 Simplifying u = -4

Subproblem 2

Set the factor '(2 + 3u)' equal to zero and attempt to solve: Simplifying 2 + 3u = 0 Solving 2 + 3u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3u = 0 + -2 3u = 0 + -2 Combine like terms: 0 + -2 = -2 3u = -2 Divide each side by '3'. u = -0.6666666667 Simplifying u = -0.6666666667

Solution

u = {-4, -0.6666666667}

See similar equations:

| 28y+(y*y)+12=36 | | -2+2x=(-8)+(17x) | | 7g^2-8g+2=0 | | u=4(7*6+35)+7(6+1) | | 3x+11=(-49)-(9) | | 2t^3+3t^2-9t=0 | | 10=r+15 | | 20-4x=-2(x-2) | | x+0.5*15=161.25 | | 3(x-3)+4(x-4)=17 | | 26-5x=(6)-(10) | | 31-6x=13-6x | | 3+5x=35 | | -100t^2-5=0 | | -5y^2+3y+9=0 | | p(v)=2v-7 | | 20x-12+4=-2 | | 4m^3-33m^2+8m=0 | | -7b-7(5+4b)=-7b-7 | | .3(3z+6)+12.6=.6(3z-6) | | 4u^3+44u^2+121u=0 | | 7(x-8)+19=5(x-7) | | 5+7+4=5+7+4 | | (50/x)(161.25/15) | | 39=13k | | X^2-(X-2)^2=5/3 | | 5=6X+10+X | | -x+2y+3z=7 | | 3-3=15x+7x | | 50/x=161.25/15 | | -V=12V | | 3(1-8x)=32+5x |

Equations solver categories